Predicting healthcare utilization in youth with type 1 diabetes: The importance of family level variables. Issue 2 (16th November 2020) - Klostermann, Susan; Iskander, Jeannette; Enlow, Paul; Delamater, Alan M.; Dolan, Lawrence; Pendley, Jennifer Shroff
Abstract: Objective: Little is known about how family factors impacting treatment adherence in type 1 diabetes are directly associated with unplanned healthcare utilization (e.g., emergency room visits and hospital admissions). Given the substantial financial burden of diabetes, understanding predictors of healthcare utilization in particular is important to inform behavioral interventions aimed toward improving adherence. Research Design and Methods: The current study examined the relationship between family‐level variables and healthcare utilization in a sample of 239 youth with type 1 diabetes and their parents. Healthcare utilization was determined via parent report and chart review. Parent‐ and youth‐reports regarding levels of family conflict, youth autonomy, and parent support related to diabetes management were obtained via questionnaire, and negative reciprocity was obtained by coding observations of parent and youth interactions. Generalized Estimating Equations were used to examine the longitudinal association between healthcare utilization and family‐level factors. Results: Higher levels of observed negative reciprocity were associated with more frequent hospital admissions, while higher levels of youth‐reported parent involvement in diabetes management were associated with fewer hospital admissions and ED visits. Conclusions: These findings highlight how family‐level factors are directly related to healthcare utilization and point to the continued importance of integrating family‐focused behavioral interventions in routine medical care for improving type 1 diabetes outcomes and reducing healthcare costs.